Faktor - Faktor yang Mempengaruhi Minat Non Muslim Menjadi Nasabah Bank Syariah Indonesia DIY - Rahmawati, Siti; Ahyar, Ahyar; Setyono, Joko (CV. Ulil Albab Corp, 2024)
The development of Islamic banking services received a positive response among non-Muslims. This study aims to examine and analyze the factors that influence the interest of non-Muslims to become BSI Yogyakarta Special Region. The population in this study is the non-Muslim community of DIY. The data used in this study is primary data collected through the results of questionnaires and interviews with respondents. There are 120 respondents B SI Yogyakarta Special Region. The data analysis used in this study is multiple linear regression analysis using spss 23. The results of this study are the product, promotion and bank reputation variables affect the interest of non-Muslims to become BSI customers in the Special Region of Yogyakarta while the price, location, and service variables have no effect on interest in DIY non-Muslims.